2020
DOI: 10.1101/2020.03.31.018432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipose depot-specific upregulation of Ucp1 or mitochondrial oxidative complex proteins are early consequences of genetic insulin reduction in mice

Abstract: Hyperinsulinemia plays a causal role in adiposity tissue expansion. We have previously shown that mice with reduced insulin gene dosage have increased energy expenditure, but the tissue-specific molecular mechanisms involved in the effects of abrogated hyperinsulinemia have remained unclear. Herein we investigated the effects of genetically reducing insulin production on the abundance of oxidative mitochondrial complex proteins in liver, skeletal muscle, white adipose tissue and brown adipose tissue. To suppre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Thymus-specific deletion of Ins2 was reported to be sufficient to cause spontaneous diabetes, even outside the NOD background (12). Although we have not observed autoimmune diabetes in globally deficient Ins2 -/- mice (13,14) it has previously reported that male, but not female, NOD: Ins1 Neo/WT ; Ins2 -/- mice, with a single remaining Ins1 allele have been shown to succumb to insulin insufficiency (15), a finding we confirmed on other backgrounds (16). These observations were found to be dependent on housing conditions (11).…”
Section: Introductionsupporting
confidence: 77%
“…Thymus-specific deletion of Ins2 was reported to be sufficient to cause spontaneous diabetes, even outside the NOD background (12). Although we have not observed autoimmune diabetes in globally deficient Ins2 -/- mice (13,14) it has previously reported that male, but not female, NOD: Ins1 Neo/WT ; Ins2 -/- mice, with a single remaining Ins1 allele have been shown to succumb to insulin insufficiency (15), a finding we confirmed on other backgrounds (16). These observations were found to be dependent on housing conditions (11).…”
Section: Introductionsupporting
confidence: 77%
“…Energy expenditure was increased, but there was no difference in measured food intake [20]. Follow-up studies identified upregulation of oxidative phosphorylation complex proteins and uncoupling protein 1 in white adipose tissue [114]. Templeman et al [30,115] made similar observations by modulating Ins2 gene dosage in mice without Ins1.…”
Section: Hyperinsulinemia Plays a Causal Role In Obesitymentioning
confidence: 95%
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted November 16, 2021. ; https://doi.org/10.1101/2021.11.11.468339 doi: bioRxiv preprint expenditure (10). The PPARγ-NcoR complex benefited vascular endothelium insulin resistance (11).…”
Section: Introductionmentioning
confidence: 99%